Pharmaceutical clinical trial supply chain : modelling and analysis - Tan, Dennis Wei Jie (2014)
A clinical trial is a prospective research study to learn how different interventions behave in human subjects and to test drug safety and efficacy. The development phases of clinical trials in the pharmaceutical industry to bring a new drug to market are an absolutely demanding procedure. Not only it requires large expenses of up to $1 billion can take around 6 to 10 years, the chances of trial patients receiving successful drug formulation is slim. Clinical trials form the work process supply chain where patients receive medical supplies in which drugs are manufactured, packed and shipped globally to distribution centers (DCs) before distributing to clinical trial sites. The main priority is to ensure patients receive appropriate and robust medical supplies swiftly with continuous resupplying. Also to reduce total costs, more sites are opened to recruit more candidates. Organizations are trying to solve supply chain tax and price structures. To resolve these issues, many industries are working on the simulation modelling of clinical trial supply chain optimization in terms of increasing flexibility, reducing lead times and maintaining supply demands by changing trial designs, improving production efficiency and simulating demand scenario forecast. For this project, a simulation model is created to find the drug usage rate for patients at sites. The inventory levels for DCs and sites are also compared and discussed.